CASE STUDY OF A TARLOV CYST IN A SYRIAN PATIENT - Salman, Hala; Kharma , Leen; Khammash, Farah; Murad, Musab; Alquobaili, Faizeh (MNJ (Malang Neurology Journal), 2024)
Tarlov cyst is a rare disease that affects the nervous system, which is a vesicle filled with spinal cord fluid, the cyst surrounding the nerve are fluid-filled sacs that greatly affect the nerve root and are detected by magnetic resonance in some cases the bag expands and put pressure on the affected nerve root. Several treatment methods have been used, including pharmacological and non-pharmacological methods such as cortisone injections and surgery. As a result of the multiplicity of information about Tarlov’s cyst disease, a questionnaire was conducted for the project to prove the views of its being a rare disease and to find out the extent of awareness in society in differentiating between symptoms associated with Tarlov’s cyst and other neurological diseases, we found that 86.4% of people who contributed in our questionnaire were not able to identify the disease, so we found its important to study the Tarlov cyst case that was diagnosed in 2019  which belongs to a  20-year-old girl. X-ray and MRI were used to diagnose Tarlov's Cyst after one year of the first visit to the doctor. After treating the cyst with muscle relaxants and cortisone for one year the pain persisted and surgery was carried out in 2021.  Late diagnosis is common and the degree of knowledge of the disease is low even among medical practitioners. Therefore, we concluded that awareness must be spread through increased research and scientific seminars to introduce it, especially with regard to the medical branches.